The Effect of Purchase Intention on TikTok E-Commerce Live Streaming: Generation Z Perspective with Customer Engagement - Retnosari, Marda; Nadlifatin, Reny (LifeSciFi, 2024)
The expansion of digital technology has transformed e-commerce, with live-streaming platforms like TikTok becoming popular among Generation Z in Indonesia. Despite their high consumption rates, engaging Gen Z poses challenges for marketers. This study examines the influence of trust, flow experience, and perceived value on purchase intention, with customer engagement as a mediator and deal proneness as a moderator, using SOR theory. A quantitative method was adopted with 402 Gen Z respondents who use TikTok live-streaming e-commerce in Jakarta. Data collection involved questionnaires analyzed through PLS-SEM and chi-square tabulations. Findings reveal that trust in product does not significantly influence customer engagement, and customer engagement has an insignificant direct effect on purchase intention. However, it partially mediates purchase intention, while deal proneness does not strengthen this relationship. Control variables, including transaction frequency, gender, viewing duration, and occupation, showed no significant impact on purchase intention. These results suggest that Gen Z demonstrates prudence in TikTok transactions. Managerial implications highlight the need for e-commerce businesses to adapt strategies to suit Gen Z's characteristics. Enhancing product trust through quality improvements and leveraging trusted broadcasters can boost engagement and purchase intent. Transparent platforms and clear communication of product value during live streams are essential. Prioritizing data analytics to understand customer preferences and mitigate online shopping risks can create a positive shopping experience, driving Gen Z's purchase intention. Interactive content and secure platforms are crucial for fostering trust and loyalty in this demographic.